Has Europe learned the lessons of territory? An African perspective on Oscar Mazzoleni’s book - Jirari, Mouna (The Greek Review of Social Research, 2025)
In his book, Territory and democratic politics: A critical introduction (2024), Oscar Mazzoleni reflects upon territory, and the outcome this notion creates. He pushes back against the trend of "deterritorialization" in social sciences and underlines a need for a correct understanding of territory for management of late modernity issues inclusive of citizenship, nationalism and migration. Mazzoleni further opined that ‘territory can hardly be understood as an area or a geographical space but it is an aspect of identities and politics’. Within this context, by dwelling on the territory/identity/power connection, Mazzoleni offers valuable insights into most of the problems that affect democracies today. This review contextualizes and refines Mazzoleni’s work through a lens by addressing fundamental issues related to the African context. The purpose of this article is to deconstruct the arduous nature of the land and the dynamics of democratization in Africa, which still lags in responding to the challenges of decolonization, not to mention the colonial invention of borders and nations.